Penggunaan Aplikasi Stroberi Kasir pada Pelaku Umkm Opak - Viola De Yusa; Zuriana; Besti Lilyana; Fabia Nabila (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
In the era of the development of science and technology as well as the high level of competition in the business world is a challenge that must be faced by all parties, especially in Micro, Small and Medium Enterprises (MSMEs). In Wonodadi village, the majority are Javanese and are Muslim who have SMEs in opaque businesses made from cassava. These MSME actors have only used their financial records manually so that there are often significant errors in terms of finances. Based on these problems, we do service with the aim of providing an understanding of recording transactions using applications and how to use them, as well as providing information , explains how to develop Micro, Small and Medium Enterprises using the Strawberry Cashier Application. and Helping and teaching people who have MSMEs to create accounts in the strawberry cashier application and how to input financial income and expenses. The method that we do is starting with socialization by introducing and explaining the use of digital-based transaction recording, namely the Strawberry Cashier Application to MSME actors and assisting MSME actors in creating accounts in the strawberry cashier application and helping input MSME Financial transactions in the application. directly to SMEs). The partners of the MSMEs are the owners of MSMEs processed by opaque Mak Friska and the Karang Taruna Wonodadi Village.